Analisis Kajian Sastra Ekspresif dan Unsur Intrinsik Pada Puisi “Ibu” Karya Kh. Musthofa Bisri (Jurnal Sosial Humaniora dan Pendidikan, 2023)
This article aims to (1) analyze expressive literary studies and intrinsic elements in the poem entitled "Ibu" by KH. Musthofa Bisri (2) describes the analysis of expressive literary works and the intrinsic elements of poetry. The method used is a qualitative descriptive research method. The data analysis used went through several stages, namely literature study by searching for information then reading, then taking notes and identifying lines of poetry which are included in the intrinsic elements of poetry. From the results obtained from the poem entitled "Ibu" by KH. Musthofa Bisri has several elements intrinsic to expressive analytical literary studies.